Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: 1. The role of Internal Audit in reducing Financial Risks (Applying to Companies listed in the Saudi Stock Exchange) Asst-Prof. Elsamani Ataelmanan Abdelrahim , Asst-Prof. Mai Osman Ali Abbu 2. The impact of applying international standards for professional project management on the quality of projects: an applied study on the projects of the Ministry of Health in Makkah Al-Mukarramah Mr. Fahd Mohammed Ahmed Al-Zahrani, Dr. Nadin Fahad Al-Madani 3. The extent of application of digital transformation standards to the management of the services of the Ministry of Justice, Madinah branch, from the staff viewpoint Dr. Majed Attia Al-Sulami, Dr. Dana Munther Rajkhan, Ms. Hadeel Khalaf Al-Mutairi 4. The reality of financial inclusion in Sudanese banks Dr. Omer Mahgoub El-Hussein 5. Legal provisions for the depositary bank in the cash deposit contract according to Yemeni law “A comparative study" Mr. Hussein Ahmed Saleh Al-Shaddadi 6. The impact of sugar projects on the community of White Nile State - Sudan Co-Prof. Mohamed Abdalla Mohamed Ahmed 7. Indicators of political stability within growth theory and its impact on the growth of the industrial sector in Saudi Arabia (An Empirical Study for the period 1998-2022) Ms. Taibah Abdul-Hamid Saqr, Dr. Lamia Saud Shesha 8. The impact of electronic accounting disclosure on the quality of accounting information: An applied study on commercial banks in Sudan Dr. Nagwa Mohamed Bahreldin